Adapting a Fourier pseudospectral method to Dirichlet boundary conditions for Rayleigh–Bénard convection - Ramos, Ivana Carola; Briozzo, Carlos Bruno (2022)
Fil: Ramos, Ivana Carola. Universidad Nacional de Córdoba. Facultad de Matemática, Astronomía y Física; Argentina.